Governing the unemployable in the neurochemical age? The case of disability coding at the Public Employment Service. Issue 4 (December 2018) - Sunnerfjell, Jon; Jacobsson, Kerstin
Abstract This article considers the practice of disability detection and coding in the Swedish Public Employment Service (PES). By investigating and contrasting the governmental techniques for handling the category of 'unemployable' subjects on the one hand, and the self-understanding and 'work on the self' by the coded individuals on the other, it researches the role that the PES plays in the shaping of 'disabled subjectivities'. Drawing on Dean's analytical distinction, the analysis here contrasts two modes of subjectification: 'governmental' versus 'ethical' self-formation. By doing so, the article gives meaning to the fact that clients diagnosed with, or who aspire on receiving, neuropsychiatric diagnoses may sometimes refuse to view themselves as 'disabled'. In such cases, a neuropsychiatric diagnosis may in fact constitute a platform for resisting governmentally encouraged subject-positions.